Influence of gender on career expectations of oral and maxillofacial surgeons. Issue 4 (April 2020) - Abu-Hammad, Shaden; Elsayed, Shadia A.; Nourwali, Ibrahim; Abu-Hammad, Osama; Sghaireen, Mohammed; Abouzaid, Basant Hamdy; Dar-Odeh, Najla
Abstract: Objectives: This study aimed to explore gender differences on career satisfaction among oral and maxillofacial surgeons (OMFS) and to compare their views on female gender representation in leadership and mentorship positions. Methods: A questionnaire was distributed among a sample of female and male OMFS surgeons in Egypt, Jordan and Saudi Arabia. Data were statistically analyzed to calculate significant differences between gender groups. Results: A total of 110 (70 males and 40 females) or (18.7%) of a total of 587 (OMFS) surgeons in the three countries participated. Respondents had a mean age of: 39.2 ± 9.0 years (range = 25–60 years). Significantly more males (60) than females (24) indicated satisfaction with their careers (P = 0.008), and significantly more males (66) than females (23) thought that OMFS is the right specialty for them (P < 0.001). Also significantly more males (31) than females (9) indicated OMFS should be solely practiced by males (P = 0.025). On the other hand, significantly more females (20) than males (7) thought that females possess certain qualities that make them more suitable for OMFS (P < 0.001); and more females (27) than males (32) believed that females are under-represented in OMFS (P = 0.031). Significantly more females (25) than males (27) believed that female OMFS surgeons tend to be single or to get divorced (P = 0.018). Males and females were in agreement that females are under-represented in leadership and mentorship positions (P = 0.561). Conclusions: Females OMFS surgeons are less satisfied with their career than their male peers. It seems that female surgeons are under-represented in the profession especially as leaders and mentors. Socially, more female OMFS surgeons than males tend to be single and this may be correlated with the surgical career.